2019
DOI: 10.1097/ncc.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of the Turkish Version of the Lymphedema Life Impact Scale in Patients With Breast Cancer–Related Lymphedema

Abstract: Background Health-related quality of life is measured to detect the influence of lymphedema on physical, functional, and social aspects of life in patients with breast cancer–related lymphedema (BCRL). Objective This study aimed to perform the psychometric evaluation of the Lymphedema Life Impact Scale (LLIS) in Turkish patients with BCRL. Methods Patients with BCRL (n = 78) filled out the Turkish LLIS, Lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
3
9
0
1
Order By: Relevance
“…In the present study, the results of EFA supporting the structure of the original structure, EFA of the Arabic version of LLIS identified three factors namely physical, psychological, and functional. Similar to the results obtained in the original study, Turkish and Persian versions of LLIS …”
Section: Patients’ Characteristic (N = 90)supporting
confidence: 66%
See 2 more Smart Citations
“…In the present study, the results of EFA supporting the structure of the original structure, EFA of the Arabic version of LLIS identified three factors namely physical, psychological, and functional. Similar to the results obtained in the original study, Turkish and Persian versions of LLIS …”
Section: Patients’ Characteristic (N = 90)supporting
confidence: 66%
“…Furthermore, the current findings indicated that there were strong positive relationships between LLIS subscales and symptom domain of EORTC QLQ-C30 (0.73, 0.81, and 0.81, respectively). Similar findings were obtained byOrhan, C., et al (2019). Moderate relationships were found between LLIS subscales and symptom domain of EORTC QLQ-C30 among Turkish patients (0.68, 0.67, and 0.67, respectively) 9.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…For instance, breast cancer-related lymphedema (BCRL) is commonplace in musculoskeletal practice and has the potential to cause significant disability during daily activities [1]. Therefore, in addition to lymphedema, breast cancer patients might also suffer other conditions after surgery, radiotherapy, or chemotherapy, such as neuropathy up to 30%, myofascial pain up to 44%, fatigue up to 94%, 20-40% upper body problems, and 18-54% functional limitations [2][3][4][5][6][7][8], which contribute to patients' particular complaints, such as arm pain, numbness, or feeling of heaviness [9,10]. Women with lymphedema more frequently report pain and demonstrate bilateral impairments in shoulder range of motion, greater restrictions in upper limb activities and upper limb strength, and sensory disturbances compared to women without lymphedema [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…sensory disturbances due to neuropathic problems after surgery, radiotherapy or chemotherapy) that contribute to patients' particular complaints like arm pain, numbness or feeling of heaviness, etc. [2,3]. While there are already/several studies in the literature on physical, functional, emotional problems; the effects of lymphedema on sensory parameters have not been explored until now.…”
Section: Introductionmentioning
confidence: 99%